A ceramicized silicone rubber material, its preparation method and application

CN122917548APending Publication Date: 2026-10-16HUNANVALIN WIRE&CABLE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611360488.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有技术制备陶瓷化硅橡胶时,大多依靠添加单一补强填料以提高初始强度,或是单纯加大成瓷填料的用量来改善成瓷效果,其间存在难以调和的技术矛盾:单一补强填料和硅橡胶基体界面适配性差,容易发生团聚,对初始力学强度的提升幅度有限,高温环境下还易分解失效,失去补强作用;若过量加入成瓷填料,又会削弱硅橡胶基体的弹性,造成断裂伸长率明显下降

Benefits of technology

本发明通过硼硅玻璃粉与改性云母粉复配成瓷、改性膨胀石墨与纳米氢氧化镁配合阻燃,并结合复合补强填料与交联改性体系,在显著提升材料常温力学强度与断裂伸长率的同时,大幅优化了高温成瓷致密度与弯曲强度,实现了阻燃性能与结构稳定性同步增强,综合性能明显优于传统陶瓷化硅橡胶,具备优异的应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917548A_ABST
    Figure CN122917548A_ABST
Patent Text Reader

Abstract

The application provides a ceramifiable silicone rubber material and a preparation method and application thereof. The ceramifiable silicone rubber material comprises the following preparation raw materials: 100 parts of a silicone rubber matrix, 35-50 parts of a composite reinforcing filler, 25-40 parts of a porcelainizing agent, 15-25 parts of a flame-retardant synergist, 5-8 parts of a cross-linking modifier, 3-6 parts of a vulcanizing agent and 2-5 parts of an interface compatibilizer. The preparation raw materials of the porcelainizing agent comprise borosilicate glass powder and modified mica powder. The modified mica powder is titanium ester coupling agent modified mica powder. The preparation raw materials of the flame-retardant synergist comprise modified expanded graphite and nano magnesium hydroxide. The preparation raw materials of the modified expanded graphite comprise cetyltrimethylammonium chloride, ammonium polyphosphate and expanded graphite. The ceramifiable silicone rubber material with excellent mechanical properties, high-temperature ceramifiable dense high strength and outstanding flame-retardant effect is obtained by compounding the porcelainizing agent, the flame-retardant synergist and the reinforcing cross-linking system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of silicone rubber composite materials technology, and in particular to a ceramicized silicone rubber material and its preparation method and application. Background Technology

[0002] Ceramicized silicone rubber is a new type of functional material. At room temperature, it has the excellent resilience and flexibility of silicone rubber. When exposed to high-temperature flames, it can be sintered to form a continuous and dense ceramic hard shell, which can effectively block the spread of flames and heat conduction, while maintaining stable insulation performance and a complete overall structure. It is now widely used in the fields of new energy vehicle battery pack protection, power cable sheathing, and fire protection of petrochemical pipelines.

[0003] In the current technology for preparing ceramicized silicone rubber, most methods rely on adding a single reinforcing filler to improve initial strength, or simply increasing the amount of ceramic-forming filler to improve the ceramicization effect. However, this approach presents inherent technical contradictions: single reinforcing fillers have poor interfacial compatibility with the silicone rubber matrix, easily leading to agglomeration and limited improvement in initial mechanical strength. Furthermore, they are prone to decomposition and failure at high temperatures, losing their reinforcing effect. On the other hand, excessive addition of ceramic-forming fillers weakens the elasticity of the silicone rubber matrix, resulting in a significant decrease in elongation at break. Simultaneously, the sintering reaction in traditional ceramicization systems is incomplete, resulting in a ceramic body with excessive porosity and low density after ablation, making it difficult to meet the insulation resistance and structural strength requirements of wires and cables under extreme operating conditions.

[0004] In addition, traditional ceramicized silicone rubber often uses conventional expanded graphite, magnesium hydroxide and other single flame-retardant raw materials, which have a general flame-retardant improvement effect, and are prone to pores during high-temperature ceramicization process, which further reduces the density and mechanical strength of the ceramic body. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a ceramicized silicone rubber material with good flame retardant effect and mechanical strength.

[0006] Specifically, the first aspect of this application provides a ceramicized silicone rubber material, comprising the following raw materials in parts by weight: 100 parts of silicone rubber matrix, 35 to 50 parts of composite reinforcing filler, 25 to 40 parts of ceramicizing agent, 15 to 25 parts of flame retardant synergist, 5 to 8 parts of crosslinking modifier, 3 to 6 parts of vulcanizing agent, and 2 to 5 parts of interface compatibilizer; The raw materials for preparing the ceramic-forming agent include borosilicate glass powder and modified mica powder; The modified mica powder is a mica powder modified with a titanate coupling agent; The raw materials for preparing the flame retardant synergist include modified expanded graphite and nano-magnesium hydroxide; The raw materials for preparing the modified expanded graphite include hexadecyltrimethylammonium chloride, ammonium polyphosphate, and expanded graphite.

[0007] This ceramicized silicone rubber material has the following beneficial effects: This invention combines borosilicate glass powder and modified mica powder to form ceramic, modified expanded graphite and nano-magnesium hydroxide for flame retardancy, and combines composite reinforcing fillers and cross-linking modification systems. While significantly improving the material's room temperature mechanical strength and elongation at break, it also greatly optimizes the high-temperature ceramic density and flexural strength, achieving simultaneous enhancement of flame retardancy and structural stability. Its comprehensive performance is significantly better than traditional ceramicized silicone rubber, and it has excellent application value.

[0008] According to some embodiments of the present invention, the silicone rubber matrix is ​​methyl vinyl silicone rubber and phenyl silicone rubber.

[0009] According to some embodiments of the present invention, the mass ratio of methyl vinyl silicone rubber to phenyl silicone rubber in the silicone rubber matrix is ​​1.5~2.5:1.

[0010] According to some embodiments of the present invention, the vinyl molar content of the methyl vinyl silicone rubber is 0.8% to 1.2%.

[0011] According to some embodiments of the present invention, the number average molecular weight of the methyl vinyl silicone rubber is 800,000 to 1,000,000.

[0012] According to some embodiments of the present invention, the phenyl molar content of the phenyl silicone rubber is 10% to 15%.

[0013] According to some embodiments of the present invention, the number-average molecular weight of the phenyl silicone rubber is 600,000 to 800,000.

[0014] Methyl vinyl silicone rubber with high vinyl content can increase crosslinking density and improve initial tensile strength. The phenyl structure of phenyl silicone rubber can improve the high temperature resistance of silicone rubber, avoid matrix degradation at high temperatures, and ensure the structural integrity of the matrix during the ceramic formation process.

[0015] According to some embodiments of the present invention, the composite reinforcing filler is modified short-cut quartz fiber and silica.

[0016] According to some embodiments of the present invention, in the composite reinforcing filler, the mass ratio of silica to modified chopped quartz fiber is 1.5~2.5:1.

[0017] According to some embodiments of the present invention, the modified chopped quartz fiber is an aminosilane modified quartz fiber.

[0018] Silica has high hardness and excellent high temperature resistance, which can significantly improve the initial tensile strength of silicone rubber. Short-cut quartz fibers modified with silane coupling agents have significantly improved interfacial compatibility with the silicone rubber matrix, avoiding agglomeration. At the same time, during the ceramic formation process, short-cut quartz fibers can serve as the skeleton of the ceramic body, improving the density and strength of the ceramic.

[0019] According to some embodiments of the present invention, the softening point of the borosilicate glass powder is 450°C to 550°C.

[0020] According to some embodiments of the present invention, the particle size of the borosilicate glass powder is 100nm~200nm.

[0021] Borosilicate glass powder melts first at high temperature to form a glass phase binder, which binds together the ablated silicone rubber carbon residue, reinforcing fillers, etc. The layered structure of modified mica powder can form a dense barrier layer in the ceramic body. At the same time, the lamellar structure of mica powder can fill the pores of the glass phase, significantly reducing the porosity of the ceramic body and improving the density and flexural strength of the ceramic.

[0022] According to some embodiments of the present invention, the mass ratio of borosilicate glass powder to modified mica powder in the ceramic forming agent is 2.5~3.5:1.

[0023] According to some embodiments of the present invention, in the flame retardant synergist, the mass ratio of modified expanded graphite to nano magnesium hydroxide is 1.5~2.5:1.

[0024] Modified expanded graphite expands rapidly when heated, forming a dense carbon layer that blocks flames and heat. Nano-magnesium hydroxide decomposes and absorbs heat when heated, releasing water vapor to dilute flammable gases. The two work together to retard flames. Furthermore, the expanded graphite modified with ammonium polyphosphate can react with the glass phase during the ceramic forming process to form phosphobosilicate ceramics, further improving the density of the ceramic.

[0025] According to some embodiments of the present invention, the expansion volume of the modified expanded graphite is 300 mL / g to 350 mL / g.

[0026] According to some embodiments of the present invention, the crosslinking modifier is a polysiloxane microcrosslinking agent and trimethylolpropane trimethacrylate.

[0027] According to some embodiments of the present invention, in the crosslinking modifier, the mass ratio of polysiloxane microcrosslinking agent and trimethylolpropane trimethacrylate is 1:0.5~1.5.

[0028] Crosslinking modifiers can improve the crosslinking density and crosslinking uniformity of silicone rubber. Polysiloxane micro-crosslinking agents have good compatibility with the silicone rubber matrix and can form micro-crosslinking points. While improving the initial strength, they can also ensure the elongation at break of silicone rubber and prevent it from becoming brittle.

[0029] According to some embodiments of the present invention, the vulcanizing agent is dicumyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane.

[0030] According to some embodiments of the present invention, in the vulcanizing agent, the mass ratio of dicumyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane is 1:1.5~2.5.

[0031] According to some embodiments of the present invention, the interface compatibilizer is a polyether-modified polysiloxane.

[0032] According to some embodiments of the present invention, the polysiloxane microcrosslinking agent is vinyl-terminated polydimethylsiloxane microspheres.

[0033] According to some embodiments of the present invention, the particle size of the polysiloxane microcrosslinker is 200 nm to 300 nm.

[0034] According to some embodiments of the present invention, the hydroxyl value of the polyether-modified polysiloxane is 50 mg KOH / g to 80 mg KOH / g.

[0035] Compound vulcanizing agents can control the vulcanization rate, ensuring sufficient vulcanization without over-vulcanization. Interface compatibilizers can reduce the interfacial tension between each filler and the silicone rubber matrix, improve the dispersibility of the fillers, and further enhance the initial mechanical properties of silicone rubber.

[0036] According to some embodiments of the present invention, the modified mica powder is prepared as follows: Mix mica powder with titanate coupling agent.

[0037] According to some embodiments of the present invention, the mass ratio of mica powder to titanate coupling agent is 100:2~3.

[0038] According to some embodiments of the present invention, the mixing temperature is 80°C to 90°C.

[0039] According to some embodiments of the present invention, the mixing time is 8 min to 15 min.

[0040] According to some embodiments of the present invention, the modified expanded graphite is prepared as follows: S1: After mixing expanded graphite with an aqueous solution of hexadecyltrimethylammonium chloride, solid-liquid separation is performed, and the solid phase is collected; S2: Mix the solid phase with ammonium polyphosphate.

[0041] According to some embodiments of the present invention, in step S1, the mixing temperature is 50°C to 70°C.

[0042] According to some embodiments of the present invention, in step S1, the mixing time is 0.5h to 1.5h.

[0043] According to some embodiments of the present invention, in step S2, the mixing temperature is 90°C to 110°C.

[0044] According to some embodiments of the present invention, in step S2, the mixing process is carried out under vacuum conditions.

[0045] According to some embodiments of the present invention, in step S2, the vacuum degree of the mixing process is -0.09MPa to -0.01MPa.

[0046] According to some embodiments of the present invention, in step S2, the mixing time is 10 min to 20 min.

[0047] According to some embodiments of the present invention, the mass ratio of expanded graphite to hexadecyltrimethylammonium chloride is 100:2~5.

[0048] According to some embodiments of the present invention, the mass ratio of expanded graphite to ammonium polyphosphate is 100:4~6.

[0049] According to some embodiments of the present invention, the modified chopped quartz fiber is prepared as follows: Short-cut quartz fibers are mixed with aminosilane.

[0050] According to some embodiments of the present invention, the aminosilane is γ-aminopropyltriethoxysilane.

[0051] According to some embodiments of the present invention, the mass ratio of the chopped quartz fiber to aminosilane is 100:2~5.

[0052] According to some embodiments of the present invention, the mixing temperature is 70°C to 90°C.

[0053] According to some embodiments of the present invention, the mixing time is 1.5h to 2.5h.

[0054] A second aspect of this application provides a method for preparing the above-mentioned ceramicized silicone rubber material, comprising the following steps: S1. Premixed modification: The composite reinforcing filler is mixed with an interface compatibilizer to obtain the modified reinforcing filler; S2. Base material mixing: The silicone rubber matrix, modified reinforcing filler, ceramic-forming agent, flame retardant synergist and crosslinking modifier are mixed to obtain the mixed base material; S3. Vulcanization compounding: Vulcanizing agent is added to the compounding base material and compounded to obtain vulcanized rubber compound; S4. Step vulcanization: The vulcanized rubber compound is subjected to primary vulcanization and secondary vulcanization.

[0055] According to some embodiments of the present invention, in step S1, intermittent ultrasound assistance is used during the mixing process.

[0056] According to some embodiments of the present invention, in step S1, the ultrasonic power of the intermittent ultrasound-assisted ultrasound is 300W~400W.

[0057] According to some embodiments of the present invention, in step S1, the ultrasound duration of intermittent ultrasound-assisted ultrasound is 4s to 6s.

[0058] According to some embodiments of the present invention, in step S1, the interval time of the intermittent ultrasound-assisted ultrasound process is 8s to 12s.

[0059] According to some embodiments of the present invention, the temperature during the mixing process is 80°C to 90°C.

[0060] According to some embodiments of the present invention, the rotational speed during the mixing process is 1500 r / min to 2000 r / min.

[0061] According to some embodiments of the present invention, step S2 is specifically as follows: S21: Kneading and plasticizing the silicone rubber matrix; S22: The modified reinforcing filler is added to the plasticized silicone rubber matrix and then mixed to obtain the first mixture; S23: Add flame retardant synergist and crosslinking modifier to the first mixture and continue mixing to obtain the mixed base material.

[0062] According to some embodiments of the present invention, in step S21, the kneading temperature is 70°C to 80°C.

[0063] According to some embodiments of the present invention, in step S21, the kneading time is 5 min to 8 min.

[0064] According to some embodiments of the present invention, in step S22, the mixing time is 25 min to 30 min.

[0065] According to some embodiments of the present invention, in step S23, the mixing time is 40 min to 50 min.

[0066] According to some embodiments of the present invention, the rotational speed during the mixing process is 60 r / min to 80 r / min.

[0067] According to some embodiments of the present invention, the temperature of the mixing process is ≤90°C.

[0068] Maintaining a temperature of ≤90℃ inside the mixing chamber is to prevent excessively high temperatures during the mixing process from causing premature cross-linking of the silicone rubber, which would affect its subsequent processing performance.

[0069] According to some embodiments of the present invention, in step S4, preheating is required before the first vulcanization.

[0070] According to some embodiments of the present invention, the temperature of the preheating process is 100°C to 110°C.

[0071] Preheating is necessary to prevent uneven cooling of the rubber compound in the mold, which could lead to uneven internal stress in the vulcanized product and affect its initial strength.

[0072] According to some embodiments of the present invention, the temperature of the primary vulcanization process is 160°C to 170°C.

[0073] According to some embodiments of the present invention, the pressure of the primary vulcanization is 12MPa to 15MPa.

[0074] According to some embodiments of the present invention, the vulcanization time is 30 min to 40 min.

[0075] According to some embodiments of the present invention, the temperature of the secondary vulcanization is 190°C to 200°C.

[0076] According to some embodiments of the present invention, the secondary vulcanization time is 120 min to 150 min.

[0077] The third aspect of this application provides an application of the above-mentioned ceramicized silicone rubber material in the fields of new energy, power, and petrochemicals. Attached Figure Description

[0078] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0079] Figure 1 The image shown is a SEM image of Example 1 after treatment at 600℃ for 1 hour. Figure 2 The image shown is a SEM image of Comparative Example 2 after treatment at 600℃ for 1 hour.

[0080] The purpose, features, and advantages of this accompanying drawing will be further explained in conjunction with the embodiments and with reference to the accompanying drawing. Detailed Implementation

[0081] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0082] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0083] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0084] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0085] The following are some of the raw materials used in the embodiments of this application: The high vinyl methyl vinyl silicone rubber selected is grade MVQ110-8; The phenyl silicone rubber used is grade HCR 785, with a phenyl molar content of 12%. The silica used is grade AEROSIL 300; The short-cut quartz fiber used is brand name FQM from Feilihua; The selected γ-aminopropyltriethoxysilane is CAS 919-30-2; The borosilicate glass powder used is grade B-3013. The sericite powder used is of brand name HY-M1; The titanate coupling agent used is NDZ-201. The expanded graphite used is grade CXKP-325, with an expansion volume of 300 mL / g to 350 mL / g. The cetyltrimethylammonium chloride used is CAS 112-02-7; The ammonium polyphosphate selected is CAS 68333-79-9; The nano-magnesium hydroxide used is grade ZH-MgOH-01 with a particle size of 50nm~100nm; The trimethylolpropane trimethacrylate used is CAS 3290-92-4; The vinyl-terminated polydimethylsiloxane used is CAS 68083-19-2; The 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane used is CAS 78-63-7; The polyether-modified polysiloxane used is AC-8410.

[0086] Example 1 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts of silicone rubber matrix, 40 parts of composite reinforcing filler, 30 parts of ceramicizing agent, 20 parts of flame retardant synergist, 6 parts of crosslinking modifier, 4 parts of vulcanizing agent, and 3 parts of interface compatibilizer. The silicone rubber matrix is ​​methyl vinyl silicone rubber with a vinyl content of 1.0% and a number average molecular weight of 900,000, which is compounded with phenyl silicone rubber with a phenyl content of 12% and a number average molecular weight of 700,000 at a mass ratio of 2:1. The composite reinforcing filler is a mixture of 60nm silica and modified short-cut quartz fiber in a mass ratio of 1.5:1. The ceramic-forming agent is a mixture of borosilicate glass powder with a softening point of 480℃ and a particle size of 150nm and modified mica powder in a mass ratio of 3:1. The flame retardant synergist is a mixture of modified expanded graphite with an expansion volume of 320 mL / g and nano-magnesium hydroxide at a mass ratio of 2:1. The crosslinking modifier is a mixture of trimethylolpropane trimethacrylate and vinyl-terminated polydimethylsiloxane microspheres with a particle size of 250 nm in a mass ratio of 1:1. The vulcanizing agent is a mixture of dicumyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane in a mass ratio of 1:2; The interface compatibilizer is a polyether-modified polysiloxane with a hydroxyl value of 65 mg KOH / g.

[0087] The preparation method of modified chopped quartz fiber is as follows: Short-cut quartz fibers and γ-aminopropyltriethoxysilane were added to an ethanol aqueous solution at a mass ratio of 100:3, dispersed for 30 min, stirred at 80 °C for 2 h, and the solid phase was collected and dried at 60 °C for 12 h to obtain modified short-cut quartz fibers.

[0088] The preparation method of modified mica powder is as follows: Modified mica powder was obtained by mixing sericite powder and titanate coupling agent at a mass ratio of 100:2 at 90℃ for 10 min.

[0089] The preparation method of modified expanded graphite is as follows: Expanded graphite was added to an aqueous solution of hexadecyltrimethylammonium chloride and stirred at 60°C for 1 hour. The solid was collected and dried at 60°C for 12 hours. The dried solid was then mixed with ammonium polyphosphate at 100°C under a vacuum of -0.095 MPa for 15 minutes. Modified expanded graphite was obtained by mixing expanded graphite, hexadecyltrimethylammonium chloride, and ammonium polyphosphate in a mass ratio of 100:3:5.

[0090] The preparation method of this ceramicized silicone rubber material includes the following steps: S1. Premixed modification: The composite reinforcing filler and interface compatibilizer are mixed at 85℃ and 1800r / min for 18min. During the mixing process, intermittent ultrasonic assistance is used with an ultrasonic power of 350W, an ultrasonic time of 5s, and an interval of 10s to obtain the modified reinforcing filler; the ceramic agent is vacuum dried at 105℃ for 2.5h. S2, Base material mixing: S21: Knead and mix the silicone rubber matrix at 75°C for 6 minutes. After the silicone rubber matrix is ​​fully plasticized, add the modified reinforcing filler and mix for 28 minutes. S22: Add flame retardant synergist and crosslinking modifier, continue mixing for 45 minutes, the mixing speed is 70 r / min, the temperature is controlled by cooling water, and the temperature inside the cavity is ≤90℃ to obtain the mixed base material; S3. Vacuum Degassing: The compound base material is subjected to vacuum treatment at a vacuum degree of -0.095MPa and a temperature of 82℃ for 18 minutes, followed by cooling to 25℃. S4. Vulcanization mixing: Add vulcanizing agent to the degassed mixing base material and mix at 35°C for 12 minutes with a mixing roller gap of 0.8 mm to obtain vulcanized rubber compound. S5. Stepwise vulcanization: Place the vulcanized rubber compound in a metal mold coated with polytetrafluoroethylene, preheat to 105℃, and perform primary and secondary vulcanization. The temperature of primary vulcanization is 165℃, the pressure is 13MPa, and the time is 35min. The temperature of secondary vulcanization is 195℃, no pressure, and the time is 135min. After demolding, the ceramicized silicone rubber material is obtained.

[0091] Example 2 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts of silicone rubber matrix, 35 parts of composite reinforcing filler, 25 parts of ceramicizing agent, 15 parts of flame retardant synergist, 5 parts of crosslinking modifier, 3 parts of vulcanizing agent, and 2 parts of interface compatibilizer. The silicone rubber matrix is ​​methyl vinyl silicone rubber with a vinyl content of 0.8% and a number average molecular weight of 800,000, which is compounded with phenyl silicone rubber with a phenyl content of 10% and a number average molecular weight of 600,000 at a mass ratio of 2:1. The composite reinforcing filler is a mixture of 50nm silica and modified quartz fiber at a mass ratio of 1.5:1. The ceramic-forming agent is a mixture of borosilicate glass powder with a softening point of 450℃ and a particle size of 100nm and modified mica powder in a mass ratio of 3:1. The flame retardant synergist is a mixture of modified expanded graphite with an expansion volume of 300 mL / g and nano-magnesium hydroxide at a mass ratio of 2:1. The crosslinking modifier is a mixture of trimethylolpropane trimethacrylate and vinyl-terminated polydimethylsiloxane microspheres with a particle size of 200 nm in a mass ratio of 1:1. The vulcanizing agent is a mixture of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane and dicumyl peroxide in a mass ratio of 2:1. The interface compatibilizer is a polyether-modified polysiloxane with a hydroxyl value of 50 mg KOH / g.

[0092] The preparation processes of modified quartz fiber, modified mica powder and modified expanded graphite are the same as in Example 1; the grades of all the above raw materials are the same as in Example 1.

[0093] The preparation method of this ceramicized silicone rubber material includes the following steps: S1. Premixed modification: The composite reinforcing filler and interface compatibilizer are mixed at 80℃ and 1500r / min for 15min. During the mixing process, intermittent ultrasonic assistance is used, with an ultrasonic power of 300W, an ultrasonic time of 5s, and an interval of 10s to obtain the modified reinforcing filler; the ceramic agent is vacuum dried at 100℃ for 2h. S2, Base material mixing: S21: Mix the silicone rubber matrix at 70°C for 5 minutes, add the modified reinforcing filler, and mix for 25 minutes; S22: Add flame retardant synergist and crosslinking modifier, and continue mixing for 40 minutes. The mixing speed is 60 r / min, and the temperature is controlled by cooling water. The temperature inside the cavity is ≤90℃ to obtain the mixed base material. S3, Vacuum degassing: The mixed base material from step S2 is subjected to vacuum treatment at a vacuum degree of -0.09MPa and a temperature of 80℃ for 15 minutes, followed by cooling to 25℃. S4. Vulcanization mixing: Add vulcanizing agent to the degassed mixing base material, mix at 30°C for 10 minutes, with a mixing roller gap of 0.5 mm, to obtain vulcanized rubber compound; S5. Stepwise vulcanization: Place the vulcanized rubber compound in a metal mold coated with polytetrafluoroethylene and preheat it to 100°C. Perform primary and secondary vulcanization. The primary vulcanization conditions are: temperature 160°C, pressure 12MPa, time 30min. The secondary vulcanization conditions are: temperature 190°C, no pressure, time 120min. Demold.

[0094] Example 3 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts silicone rubber matrix, 50 parts composite reinforcing filler, 40 parts ceramicizing agent, 25 parts flame retardant synergist, 8 parts crosslinking modifier, 6 parts vulcanizing agent, and 5 parts interface compatibilizer. The silicone rubber matrix is ​​methyl vinyl silicone rubber with a vinyl content of 1.2% and a number average molecular weight of 1 million, which is compounded with phenyl silicone rubber with a phenyl content of 15% and a number average molecular weight of 800,000 at a mass ratio of 2:1. The composite reinforcing filler is a mixture of 80nm silica and modified short-cut quartz fiber in a mass ratio of 2:1. The ceramic-forming agent is a mixture of borosilicate glass powder with a softening point of 500℃ and a particle size of 200nm and modified mica powder in a mass ratio of 3:1. The flame retardant synergist is a mixture of modified expanded graphite with an expansion volume of 350 mL / g and nano-magnesium hydroxide at a mass ratio of 2:1. The crosslinking modifier is a mixture of trimethylolpropane trimethacrylate and vinyl-terminated polydimethylsiloxane microspheres with a particle size of 300 nm in a mass ratio of 1:1. The vulcanizing agent is a mixture of 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane and dicumyl peroxide in a mass ratio of 2:1. The interface compatibilizer is a polyether-modified polysiloxane with a hydroxyl value of 80 mg KOH / g.

[0095] The preparation processes of modified quartz fiber, modified mica powder and modified expanded graphite are the same as in Example 1, and the grades of all the above raw materials are the same as in Example 1.

[0096] The preparation method of this ceramicized silicone rubber material includes the following steps: S1. Premixed modification: The composite reinforcing filler and the interface compatibilizer are mixed at 90℃ and 2000r / min for 20min. During the mixing process, intermittent ultrasonic assistance is used, with an ultrasonic power of 400W, an ultrasonic time of 5s, and an interval time of 10s to obtain the modified reinforcing filler; the ceramic agent is vacuum dried at 110℃ for 3h. S2, Base material mixing: S21: Mix the silicone rubber matrix at 80°C for 8 minutes. After the matrix is ​​fully plasticized, add the modified reinforcing filler and mix for 30 minutes. S22: Add flame retardant synergist and crosslinking modifier, and continue mixing for 50 minutes. The mixing speed is 80 r / min, and the temperature is controlled by cooling water. The temperature inside the cavity is ≤90℃ to obtain the mixed base material. S3, Vacuum degassing: The mixed base material from step S2 is subjected to vacuum treatment at a vacuum degree of -0.1MPa and a temperature of 85℃ for 20 minutes, followed by cooling to 25℃. S4. Vulcanization mixing: Add vulcanizing agent to the deaerated mixing base material and mix at 40°C for 15 minutes with a mixing roller gap of 1 mm to obtain vulcanized rubber compound. S5. Stepwise vulcanization: Place the vulcanized rubber compound in a metal mold coated with polytetrafluoroethylene and preheat it to 110°C. Perform primary and secondary vulcanization. The primary vulcanization conditions are: temperature 170°C, pressure 15MPa, time 40min. The secondary vulcanization conditions are: temperature 200°C, no pressure, time 150min. Demold.

[0097] Example 4 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts silicone rubber matrix, 38 parts composite reinforcing filler, 28 parts ceramicizing agent, 18 parts flame retardant synergist, 5.5 parts crosslinking modifier, 3.5 parts vulcanizing agent, and 2.5 parts interface compatibilizer. The specifications and compounding ratios of each raw material are the same as in Example 1; The preparation processes of modified quartz fiber, modified mica powder, and modified expanded graphite are the same as in Example 1.

[0098] The preparation method of this ceramicized silicone rubber material is basically the same as that in Example 1, with the difference being: (1) In step S1, the mixing temperature is 82℃, the rotation speed is 1600r / min, the mixing time is 16min, and the ultrasonic power is 320W; (2) In step S2, the mixing time is 5.5 min, in step S21 the mixing time is 26 min, in step S22 the mixing time is 42 min, and the rotation speed during the mixing process is 65 r / min. (3) In step S3, the vacuum degree is -0.092MPa, the temperature is 81℃, and the degassing time is 16min; (4) In step S4, the mixing temperature is 32℃, the mixing time is 11min, and the roller gap is 0.6mm; (5) In step S5, the mold preheating temperature is 102℃, the primary vulcanization temperature is 162℃, the primary vulcanization pressure is 12.5MPa, and the time is 32min; the secondary vulcanization temperature is 192℃, and the time is 125min.

[0099] Example 5 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts silicone rubber matrix, 42 parts composite reinforcing filler, 32 parts ceramicizing agent, 22 parts flame retardant synergist, 6.5 parts crosslinking modifier, 4.5 parts vulcanizing agent, and 3.5 parts interface compatibilizer. The specifications and compounding ratios of each raw material are the same as in Example 1; The preparation processes of modified quartz fiber, modified mica powder, and modified expanded graphite are the same as in Example 1.

[0100] The preparation method of this ceramicized silicone rubber material is basically the same as that in Example 1, with the difference being: (1) In step S1, the mixing temperature is 86℃, the rotation speed is 1900r / min, the mixing time is 19min, and the ultrasonic power is 360W; (2) In step S2, the mixing time is 6.5 min, the mixing time in step S21 is 29 min, the mixing time in step S22 is 46 min, and the rotation speed during the mixing process is 75 r / min. (3) In step S3, the vacuum degree is -0.096MPa, the temperature is 83℃, and the degassing time is 19min; (4) In step S4, the mixing temperature is 36℃, the mixing time is 13min, and the roller gap is 0.9mm; (5) In step S5, the preheating temperature of the mold is 106℃, the temperature of the first vulcanization is 166℃, the pressure of the first vulcanization is 13.5MPa, and the time is 36min; the temperature of the second vulcanization is 196℃, and the time of the second vulcanization is 138min.

[0101] Example 6 A ceramicized silicone rubber material comprises the following raw materials in parts by weight: 100 parts silicone rubber matrix, 46 parts composite reinforcing filler, 36 parts ceramicizing agent, 24 parts flame retardant synergist, 7.5 parts crosslinking modifier, 5.5 parts vulcanizing agent, and 4.5 parts interface compatibilizer. The specifications and compounding ratios of each raw material are the same as in Example 1; The preparation process of modified quartz fiber, modified mica powder and modified expanded graphite is the same as in Example 1.

[0102] The preparation method of this ceramicized silicone rubber material is basically the same as that in Example 1, with the difference being: (1) In step S1, the mixing temperature is 88℃, the rotation speed is 1900r / min, the mixing time is 19min, and the ultrasonic power is 380W; (2) In step S2, the mixing time is 7.5 min, the mixing time in step S21 is 29 min, the mixing time in step S22 is 48 min, and the rotation speed during the mixing process is 78 r / min. (3) In step S3, the vacuum degree is -0.098MPa, the temperature is 84℃, and the degassing time is 19min; (4) In step S4, the mixing temperature is 38℃, the mixing time is 14min, and the roller gap is 0.9mm; (5) In step S5, the mold preheating temperature is 108℃, the primary vulcanization temperature is 168℃, the pressure is 14.5MPa, and the time is 38min; the secondary vulcanization temperature is 198℃, and the time is 145min.

[0103] Example 7 A ceramicized silicone rubber material, wherein the specifications and proportions of each raw material used in its preparation are the same as those in Example 1.

[0104] The preparation method of this ceramicized silicone rubber material differs from that of Example 1 in that: Ultrasonic-assisted mixing was not used in step S1.

[0105] Example 8 A ceramicized silicone rubber material, wherein the specifications and proportions of each raw material used in its preparation are the same as those in Example 1.

[0106] The preparation method of this ceramicized silicone rubber material differs from that of Example 1 in that: The mold was not preheated in step S5.

[0107] Comparative Example 1 The ceramicized silicone rubber material differs from the raw materials in the specifications and proportions of Example 1 in that: (1) The silicone rubber matrix is ​​a single methyl vinyl silicone rubber with a vinyl molar content of 1.0% and a number average molecular weight of 900,000; (2) The composite reinforcing filler is a single type of silica with a particle size of 60 nm.

[0108] The preparation method of this ceramicized silicone rubber material differs from that of Example 1 in that: (1) In step S1, the composite reinforcing filler is replaced with silica with a single particle size of 60 nm; (2) In step S2, the silicone rubber matrix is ​​replaced with a single methyl vinyl silicone rubber with a vinyl molar content of 1.0% and a number average molecular weight of 900,000.

[0109] Comparative Example 2 The ceramicized silicone rubber material differs from the raw materials in the specifications and proportions of Example 1 in that: The ceramic-forming agent is a single borosilicate glass powder with a softening point of 480℃ and a particle size of 150nm.

[0110] The preparation method of this ceramicized silicone rubber material differs from that of Example 1 in that: In step S1, the ceramic-forming agent is replaced with a single borosilicate glass powder with a softening point of 480°C and a particle size of 150nm.

[0111] Comparative Example 3 The ceramicized silicone rubber material differs from the raw materials in the specifications and proportions of Example 1 in that: (1) No crosslinking modifier; (2) The flame retardant synergist is a single modified expanded graphite with an expansion volume of 320 mL / g.

[0112] The preparation method of this ceramicized silicone rubber material differs from that of Example 1 in that: (1) No crosslinking modifier is added in step S2; (2) In step S2, the flame retardant synergist is replaced with a single modified expanded graphite with an expansion volume of 320 mL / g.

[0113] Comparative Example 4 The ceramicized silicone rubber material differs from the raw materials in the specifications and proportions of Example 1 in that: The mass ratio of precipitated silica to modified chopped quartz fiber in the composite reinforcing filler is 3:1.

[0114] The preparation method of this ceramicized silicone rubber material is carried out in accordance with Example 1.

[0115] Comparative Example 5 The ceramicized silicone rubber material differs from the raw materials in the specifications and proportions of Example 1 in that: The vulcanizing agent is a single 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane.

[0116] The preparation method of this ceramicized silicone rubber material is carried out in accordance with Example 1.

[0117] Performance testing The ceramicized silicone rubbers prepared in each example group and the comparative example group were subjected to performance testing. The testing methods are as follows: Initial mechanical properties: tensile strength and elongation at break were tested according to GB / T 528-2009; Porcelain-forming properties: The sample was made into a strip of 80mm×10mm×3mm and placed in a tube furnace. The temperature was increased to 900℃ at 10℃ / min and held for 30min. The bending strength and bulk density (density) of the ceramic body after porcelain formation were tested. Flame retardant performance: Limiting oxygen index tested according to GB / T 10707-2008.

[0118] The test results are shown in Table 1:

[0119] As shown in Table 1, the ceramicized silicone rubbers prepared in Examples 1-6 of this application all exhibit excellent initial mechanical strength, ceramicization performance, and flame retardant properties. Their tensile strength is all above 10.5 MPa, elongation at break exceeds 400%, flexural strength after ceramicization is ≥8.1 MPa, and bulk density is ≥2.28 g / cm³. 3 The limiting oxygen index was ≥37.8%; in Example 7, the filler dispersibility was slightly reduced due to the lack of ultrasonic-assisted filler mixing, and the various properties were slightly reduced; in Example 8, the internal stress of the rubber compound was uneven after vulcanization due to the lack of preheating of the mold, and the initial strength and ceramic properties were reduced.

[0120] Comparative Example 1, due to the use of a single silicone rubber matrix and a single reinforcing filler, experienced a significant reduction in initial strength and ceramic strength, as well as a marked decrease in flame retardant performance. Comparative Example 2, lacking the pore-filling effect of modified mica powder, exhibited poor ceramic density and low ceramic flexural strength. Comparative Example 3, lacking a crosslinking modifier and employing a single flame retardant system, suffered from poor initial mechanical properties and flame retardant performance. Comparative Example 4, due to an imbalanced ratio of composite reinforcing fillers and excessive whisker silica leading to decreased matrix elasticity, resulted in a reduced initial elongation at break. Comparative Example 5, employing a single vulcanizing agent, suffered from insufficient vulcanization uniformity, affecting both initial strength and ceramic density.

[0121] Figure 1 The image shown is a SEM image of Example 1 after treatment at 600℃ for 1 hour. Figure 2 The image shows the SEM image of Comparative Example 2 after treatment at 600℃ for 1 hour. The comparison shows that the ceramic material obtained after high-temperature ceramicization in Example 1 has good density and no obvious pores; while the material obtained after high-temperature ceramicization in Comparative Example 2 has poor density and increased pores because no mica ceramicizing agent was added.

[0122] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A ceramicized silicone rubber material, characterized in that, The preparation materials include the following parts by weight: 100 parts of silicone rubber matrix, 35 to 50 parts of composite reinforcing filler, 25 to 40 parts of ceramic agent, 15 to 25 parts of flame retardant synergist, 5 to 8 parts of crosslinking modifier, 3 to 6 parts of vulcanizing agent, and 2 to 5 parts of interface compatibilizer. The raw materials for preparing the ceramic-forming agent include borosilicate glass powder and modified mica powder; The modified mica powder is a mica powder modified with a titanate coupling agent; The raw materials for preparing the flame retardant synergist include modified expanded graphite and nano-magnesium hydroxide; The raw materials for preparing the modified expanded graphite include hexadecyltrimethylammonium chloride, polyphosphoric acid, and expanded graphite.

2. The ceramicized silicone rubber material as described in claim 1, characterized in that, It satisfies at least one of the following characteristics (1) to (10): (1) The silicone rubber matrix is ​​methyl vinyl silicone rubber and phenyl silicone rubber; (2) The composite reinforcing filler is silica and modified short-cut quartz fiber; (3) The softening point of the borosilicate glass powder is 450℃~550℃; (4) The particle size of the borosilicate glass powder is 100nm~200nm; (5) In the flame retardant synergist, the mass ratio of modified expanded graphite to nano magnesium hydroxide is 1.5~2.5:1; (6) The expansion volume of the modified expanded graphite is 300 mL / g to 350 mL / g; (7) The crosslinking modifier is a polysiloxane microcrosslinking agent and trimethylolpropane trimethacrylate; (8) The vulcanizing agent is dicumyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane; (9) The interface compatibilizer is a polyether-modified polysiloxane; (10) In the ceramic-forming agent, the mass ratio of borosilicate glass powder to modified mica powder is 2.5~3.5:

1.

3. The ceramicized silicone rubber material as described in claim 2, characterized in that, It satisfies at least one of the following characteristics (1) to (12): (1) The vinyl content of the methyl vinyl silicone rubber is 0.8%~1.2%; (2) The number average molecular weight of the methyl vinyl silicone rubber is 800,000 to 1,000,000; (3) The phenyl molar content of the phenyl silicone rubber is 10%~15%; (4) The number average molecular weight of the phenyl silicone rubber is 600,000 to 800,000; (5) In the silicone rubber matrix, the mass ratio of methyl vinyl silicone rubber to phenyl silicone rubber is 1.5~2.5:1; (6) In the composite reinforcing filler, the mass ratio of silica to modified chopped quartz fiber is 1.5~2.5:1; (7) The modified short-cut quartz fiber is an aminosilane modified short-cut quartz fiber; (8) In the crosslinking modifier, the mass ratio of polysiloxane microcrosslinking agent to trimethylolpropane trimethacrylate is 1:0.5~1.5; (9) In the vulcanizing agent, the mass ratio of dicumyl peroxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane is 1:1.5~2.5; (10) The polysiloxane microcrosslinking agent is vinyl-terminated polydimethylsiloxane microspheres; (11) The particle size of the polysiloxane microcrosslinking agent is 200nm~300nm; (12) The hydroxyl value of the polyether modified polysiloxane is 50 mg KOH / g to 80 mg KOH / g.

4. A ceramicized silicone rubber material as described in claim 1 or 2, characterized in that, The modified mica powder is prepared as follows: Mix mica powder with titanate coupling agent; The mixing temperature is 80 ℃~90 ℃; The mixing time is 8 min to 15 min.

5. A ceramicized silicone rubber material as described in claim 1 or 2, characterized in that, The modified expanded graphite is prepared as follows: S1: After mixing expanded graphite with an aqueous solution of hexadecyltrimethylammonium chloride, solid-liquid separation is performed, and the solid phase is collected; S2: Mix the solid phase with ammonium polyphosphate; In step S1, the mixing temperature is 50℃~70℃; In step S1, the mixing time is 0.5h~1.5h; In step S2, the mixing temperature is 90℃~110℃; In step S2, the mixing time is 10 min to 20 min.

6. A ceramicized silicone rubber material as described in claim 2 or 3, characterized in that, The modified chopped quartz fiber is prepared as follows: Short-cut quartz fibers are mixed with aminosilane; The mixing temperature is 70 ℃~90 ℃; The mixing time is 1.5h to 2.5h.

7. A method for preparing the ceramicized silicone rubber material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Premixed modification: The composite reinforcing filler is mixed with an interface compatibilizer to obtain the modified reinforcing filler; S2. Base material mixing: The silicone rubber matrix, modified reinforcing filler, ceramic-forming agent, flame retardant synergist and crosslinking modifier are mixed to obtain the mixed base material; S3. Vulcanization compounding: Vulcanizing agent is added to the compounding base material and compounded to obtain vulcanized rubber compound; S4. Step vulcanization: The vulcanized rubber compound is subjected to primary vulcanization and secondary vulcanization.

8. The preparation method according to claim 7, characterized in that, It satisfies at least one of the following characteristics (1) to (9): (1) In step S1, intermittent ultrasound assistance is used during the mixing process; (2) In step S2, the rotation speed of the mixing process is 60 r / min to 80 r / min; (3) In step S2, the temperature of the mixing process is ≤90 ℃; (4) In step S4, preheating is performed before the first vulcanization; (5) In step S4, the temperature of the vulcanization process is 160 ℃~170 ℃; (6) In step S4, the pressure of the first vulcanization is 12 MPa to 15 MPa; (7) In step S4, the vulcanization time is 30 min to 40 min; (8) In step S4, the temperature of the secondary vulcanization is 190 ℃~200 ℃; (9) In step S4, the secondary vulcanization time is 120 min to 150 min.

9. The preparation method according to claim 8, characterized in that, It satisfies at least one of the following characteristics (1) to (4): (1) The ultrasonic power of the intermittent ultrasound-assisted ultrasound is 300W~400W; (2) The duration of the intermittent ultrasound-assisted ultrasound is 4s to 6s; (3) The interval time of the intermittent ultrasound-assisted treatment is 8s~12s; (4) The temperature of the preheating process is 100 ℃~110 ℃.

10. The application of a ceramicized silicone rubber material as described in any one of claims 1 to 6 or a ceramicized silicone rubber material prepared by any one of claims 7 to 9 in the fields of new energy, power, and petrochemicals.

Citation Information

Patent Citations

  • Cap closure

    CA112027A